Strong Selection Against Early Generation Hybrids in Joshua Tree Hybrid Zone Not Explained by Pollinators Alone - Royer, Anne M.; Waite-Himmelwright, Jackson; Smith, Christopher Irwin (Frontiers in Plant Science, 2020)
Coevolution frequently plays an important role in diversification, but the role of obligate pollination mutualisms in the maintenance of hybrid zones has rarely been investigated. Like most members of the genus Yucca, the two species of Joshua tree (Y. brevifolia and Y. jaegeriana) are involved in a tightly coevolved mutualism with yucca moths. There is strong evidence of a history of coevolution between Joshua trees and their moth pollinators. We use a geographic clines approach in the Joshua tree hybrid zone to ask if selection by the moths may currently contribute to maintaining separation between these species. We compare genomic, phenotypic, and pollinator frequency clines to test whether pollinators maintain the hybrid zone or follow it as passive participants. The results reveal dramatic overlapping genomic and pollinator clines, consistent with a narrow hybrid zone maintained by strong selection. Wider phenotypic clines and a chloroplast genomic cline displaced opposite the expected direction suggest that pollinators are not the main source of selection maintaining the hybrid zone. Rather, it seems that high levels of reproductive isolation, likely acting through multiple barriers and involving many parts of the genome, keep the hybrid zone narrow.